Distribution of Pupil Size and Associated Factors: Results from the Population-Based Gutenberg Health Study - Marian Kiel; Stephanie D. Grabitz; Susanne Hopf; Thomas Koeck; Philipp S. Wild; Irene Schmidtmann; Karl J. Lackner; Thomas Münzel; Manfred E. Beutel; Norbert Pfeiffer; Alexander K. Schuster (Journal of Ophthalmology, 2022)
Background/Objectives. The pupil regulates the incoming light to reduce glare and to achieve sufficient depth of field. Few is known on the distribution of pupil size and associated conditions in the general population. Therefore, for the first time in a large population-based study, we assess the distribution of physiologic pupil size and identify associated factors. Subjects/Methods. The Gutenberg Health Study (GHS) is a prospective cohort study established at the University Medical Center Mainz, Germany. As part of the 5-year follow-up (2012–2017), 9,559 of 12,432 participants had a valid pupil size measurement. Optical biometry (Lenstar LS900, Haag-Streit, Koeniz, Switzerland) including measurements of physical pupil diameter, central corneal thickness, corneal curvature, anterior chamber depth, and axial length was performed under mesopic light conditions. The associations of ocular geometry, the participants’ demographics, and their history of systemic diseases and medication intake with physical pupil size were assessed using multivariable linear regression models. Results. 18,335 eyes of 9,559 participants aged 40 to 80 years were included in the analysis. Median pupil diameter was 4.19 mm in right eyes and 4.12 mm in left eyes. A smaller pupil was associated with older age, hyperopic refractive error, previous cataract surgery, diabetes, obesity, and ACE inhibitor intake, whereas wider pupil was associated with female gender, arterial hypertension, intake of tricyclic antidepressants, and intake of SNRI and tetracyclic antidepressants. Socioeconomic status and smoking were not associated with pupil size. Conclusion. Individuals of older age, after cataract surgery, under therapy with ACE inhibitors and with diabetes have a smaller pupil. This should be taken into account when planning nonmydriatic fundus photography-based screening programs, for instance, for diabetic retinopathy.